Enrichment Preferences of FIV-Infected and Uninfected Laboratory-Housed Cats - Claudia J. Kennedy; Andrea E. Thomson; Emily H. Griffith; Jonathan Fogle; B. Duncan X. Lascelles; Rick B. Meeker; Barbara L. Sherman; Margaret E. Gruen (Viruses, 2018)
Environmental enrichment is critical for alleviating stress in laboratory felines. However, there is a paucity of information about suitable enrichment for cats. This study aimed to determine preferred enrichment options of individually-housed, castrated male domestic short hair cats (Felis catus) used in a longitudinal study of the effects of chronic feline immunodeficiency virus (FIV) infection, and to determine if the FIV status of the cats affected enrichment preferences. Preference testing was performed with two types of grooming brushes, three different interactive play options, including a laser, ball, and petting interaction with a familiar investigator, and two types of toenail conditioning objects. We found that cats elected to be brushed, preferred social interaction and play with the laser to the ball, and preferred to scratch on an inclined-box toenail conditioning object compared to a horizontal, circular toenail conditioning object. There were individual preferences for enrichment opportunities. There were no differences in preferences between FIV-infected and sham-infected cats. These enrichment preferences may be used to advise laboratory animal facilities and researchers about how to best accommodate the behavioral needs of laboratory cats.